Adverse event costs of systemic therapies for metastatic colorectal cancer previously treated with fluoropyrimidine-, oxaliplatinand irinotecan-based chemotherapy and biologics in the US - Victoria Federico Paly; Arvind Dasari; Joleen Hubbard; Tanios Bekaii-Saab; Thihan Padukkavidana; Luis Hernandez (Becaris Publishing Limited, 2024)
Aim: The objective of this study was to compare adverse event (AE) management costs for fruquintinib, regorafenib, trifluridine/tipiracil (T/T) and trifluridine/tipiracil+bevacizumab (T/T+bev) for patients with metastatic colorectal cancer (mCRC) previously treated with at least two prior lines of therapy from the US commercial and Medicare payer perspectives. Materials & methods: A cost-consequence model was developed to calculate the per-patient and per-patient-per-month (PPPM) AE costs using rates of grade 3/4 AEs with incidence ≥5% in clinical trials, event-specific management costs and duration treatment. Anchored comparisons of AE costs were calculated using a difference-in-differences approach with best supportive care (BSC) as a common reference. AE rates and treatment duration were obtained from clinical trials: FRESCO and FRESCO-2 (fruquintinib), RECOURSE (T/T), CORRECT (regorafenib) and SUNLIGHT (T/T, T/T+bev). AE management costs for the commercial and Medicare perspectives were obtained from publicly available sources. Results: From the commercial perspective, the AE costs (presented as perpatient, PPPM) were: $4015, $1091 for fruquintinib (FRESCO); $4253, $1390 for fruquintinib (FRESCO-2); $17,110, $11,104 for T/T (RECOURSE); $9851, $4691 for T/T (SUNLIGHT); $8199, $4823 for regorafenib; and $11,620, $2324 for T/T+bev. These results were consistent in anchored comparisons: the differencein-difference for fruquintinib based on FRESCO was -$1929 versus regorafenib and -$11,427 versus T/T; for fruquintinib based on FRESCO-2 was -$2257 versus regorafenib and -$11,756 versus T/T. Across all analyses, results were consistent from theMedicare perspective. Conclusion: Fruquintinib was associated with lower AE management costs compared with regorafenib, T/T and T/T+bev for patients with previously treated mCRC. This evidence has direct implications for treatment, formulary and pathways decision-making in this patient population.